A Data Processing Support System for the Administration of a College of Dentistry’s Student Clinics - Olde, G. L.; Bartlett, R. C. (Methods of Information in Medicine, 1974)
This report describes a data processing system which has been developed in support of the administration of the strident clinics in a college of Dentistry. By capturing data describing the work done by students on patients in the teaching clinics, a series of reporting modes have been developed which provide a capability for monitoring the progress of both patient and student. The methods used for data collection will be described along with a discussion of the various types of reports which are currently being utilized.
Keywords: Dentistry; Teaching Clinics; Administration; Student Evaluation